Factors Related to Sleep Quality of Elderly People in RW 03 Kelurahan Kebon Manggis Jakarta - Marta Cici Haryati; Indriati Kusumaningsih; Sudibyo Supardi (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIKes Panti Waluya Malang, 2022)
In the elderly, the aging process experienced causes a decrease in NREM sleep cycles 3 and 4. As a result of this decrease, it affects the sleep quality of the elderly. Sleep quality shows a person's satisfaction with his sleep, where the person does not show signs of sleep deprivation.